Liberalna dekonstrukcja systemu totalitarnego - Rau, Zbigniew (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The author outlines the argument he pursued in the last two decades of the 20th century, while working at British and American universities. In scholarly discourse of the time, the notion of totalitarianism was already abandoned in political science in general, and in sovietology in particular. Rejecting this commonly dominated position, the author assumed that the totalitarian project constituted the most radical opposition to the liberal one. Accordingly, he adopted the critical apparatus of classical liberalism, especially that of methodological individualism, to analyze totalitarianism. Above all, he used the categories of John Locke’s political thought, such as the state of nature, social contract, and especially that of civil society, as the key to understand the phenomenon of the explosion as well as implosion of totalitarianism. In fact, he assumed that the presence of civil society constituted the essence of liberal experience and its absence indicated the essence of totalitarian experience. In this interpretation, the chronological and conceptual point of departure was the state of affairs in Russia as well as in Central and Eastern Europe before the communist takeover. What dominated there could be considered a three-way social and political relationship of the individual, society and the state. The individuals constituted various associations, such as political parties, business corporations, trade unions, religious, scientific, artistic organizations or sports clubs which formed the ranks of civil society. They usually pursued different pluralistic visions of common good while influencing state policies. After the communist takeover, these three-way relationships were replaced by the two-way relationships of the individual and the Center. The latter consisted of the Communist party as well as state leadership and combined three mutually interacting branches: the political control of the police and army, the economic planning and control of economic activity and distribution, and the ideological imposition of the officially established ideology and control of the channels of mass communication. The Center destroyed the ranks of civil society and exposed the individual to its three dimensional power causing a true atomization of society. This state of affairs lasted until the emergence of dissident groups which restored pockets of civil society and deprived the Center of the ideological power over their members. The next step towards the restoration of civil society in the region was the appearance of mass vindication movements such as Solidarity in Poland in 1980, Popular Fronts in numerous Soviet Republics in 1988–1989, and in Czechoslovakia, East Germany and Bulgaria in 1989. The nationwide dimensions of these initiatives finally deprived the Center of its ideological power over the greatest part of population and considerably weakened the other two branches of its power — the economic and political ones. The political power of the Center was definitely challenged when these movements divided themselves along political lines and independent political parties emerged. The agenda of these parties was to compete with the Communists for political power in open and competitive elections. The final restoration of civil society took place when these parties managed to implement their agendas.
Keywords: totalitarianism; political thought; religious; social and political relationship